Student Perception of Sasambo's Integrated Project Based Learning (PjBL) and Ethnoscience Models to Improve Concept Understanding - Liswijaya; Agus Abhi Purwoko; Aliefman Hakim; AA Sukarso; Joni Rokhmat (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The PjBL model has been proven effective in developing critical thinking, collaboration, and creativity skills. Critical thinking, collaboration, and creativity. However, its incorporation with ethnoscience, especially in Sasambo culture, has not been widely researched. This study aims to analyze the research trends of PjBL based on ethnoscience-based PjBL research trends globally and to examine the effectiveness of Sasambo ethnoscience-based PjBL in improving the understanding of scientific concepts and appreciation of local culture. of local culture. This research is a mixed research with descriptive quantitative and bibliometric design. This research uses 2 data collection methods: bibliometric analysis with the Publish or Perish (PoP) tool and data visualization through VOSviewer, to identify research trends on ethnoscience and PjBL. Trends in research on ethnoscience and PjBL, and a questionnaire for students' understanding of ethnoscience-based PjBL. About PjBL based on Sasambo ethnoscience. The subjects involved were 30 students. The instrument used is a questionnaire sheet. After the data is collected, it is then analyzed descriptively. The results showed that the trend of PjBL-based ethnoscience-based PjBL shows great potential in strengthening high-level thinking skills. Skills. This study concludes that integrating PjBL and ethnoscience can be a practical approach in contextualized science learning based on local culture and contextualized science learning based on local culture. The implication of this research is that it is important to encourage the implementation of culture-based education in the formal curriculum to strengthen the connection between science and local wisdom among the younger generation. Among the younger generation.